Color me dark : the diary of Nellie Lee Love, the great migration North - McKissack, Pat, 1944-2017. (New York : Scholastic, 2000)
Eleven-year-old Nellie Lee Love records in her diary the events of 1919, when her family moves from Tennessee to Chicago, hoping to leave the racism and hatred of the South behind.
Keywords: African Americans -- Juvenile fiction; African Americans -- Fiction; Family life -- Fiction; Prejudices -- Fiction; Sisters -- Fiction; Diaries -- Fiction; Tennessee -- Fiction; Chicago (Ill.) -- Fiction